Підходи до електронного документообігу - Головань, С.М. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
General approaches to electronic dokumentoobigu, which need subsequent more
detailed working out in detail of prorobki of mathematical methods and analysis of estimation of efficiency and determination of different ways of realization of mechanisms of
defence, are expounded.